Pete the cat : scuba-cat - Dean, James, 1957- (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2016)
As Pete the Cat searches underwater for a seahorse, he comes into contact with all manner of sea creatures.
"My first shared reading."
250
Keywords: Cats -- Juvenile fiction; Sea horses -- Juvenile fiction; Marine animals -- Juvenile fiction; Scuba diving -- Juvenile fiction